hw8solutions(first4) - HOMEWORK ASSIGNMENT 8 PHYS852...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: HOMEWORK ASSIGNMENT 8 PHYS852 Quantum Mechanics II, Spring 2008 New topics covered: Scattering amplitude, cross-section, partial wave expansion . 1. Spherical Bessel functions: The spherical Bessel function j ℓ ( ρ ) is defined as j ℓ ( ρ ) = ( − 1) ℓ ρ ℓ parenleftbigg 1 ρ d dρ parenrightbigg ℓ sin ρ ρ . Show that this state satisfies the radial wave equation. Answer: Let j ℓ ( ρ ) = ( − 1) ℓ u ℓ ( ρ ) /ρ , where u ℓ ( ρ ) = ρ ℓ +1 parenleftbigg 1 ρ d dρ parenrightbigg ℓ sin ρ ρ The radial wave equation for u ℓ ( ρ ) is then bracketleftbigg d 2 dρ 2 − ℓ ( ℓ + 1) ρ 2 + 1 bracketrightbigg u ℓ ( ρ ) = 0 Let H ℓ = bracketleftbigg d 2 dρ 2 − ℓ ( ℓ + 1) ρ 2 + 1 bracketrightbigg Strategy: We will show that if we assume H ℓ u ℓ = 0 then we must also have H ℓ +1 u ℓ +1 = 0. Then if we establish that H u = 0, then H ℓ u ℓ = 0 for all ℓ . First we derive the recursion relation: u ℓ +1 = ρ ℓ +2 parenleftbigg 1 ρ d dρ parenrightbigg ℓ +1 sin ρ ρ = ρ ℓ +2 parenleftbigg 1 ρ d dρ parenrightbigg ρ − ℓ − 1 ρ ℓ +1 parenleftbigg 1 ρ d dρ parenrightbigg ℓ sin ρ ρ = ρ ℓ +2 parenleftbigg 1 ρ d dρ parenrightbigg ρ − ℓ − 1 u ℓ Let A = ρ ℓ +2 parenleftbigg 1 ρ d dρ parenrightbigg ρ − ℓ − 1 = bracketleftbigg d dρ − ( ℓ + 1) ρ bracketrightbigg Then we have u ℓ +1 = Au ℓ . Now we want to compute the commutator [ H ℓ ,A ] = H ℓ A = AH ℓ . First computing H ℓ A , we find bracketleftbigg d 2 dρ 2 − ℓ ( ℓ + 1) ρ 2 + 1 bracketrightbiggbracketleftbigg d dρ − ( ℓ + 1) ρ bracketrightbigg = d 3 dρ 3 + ( ℓ 2 + ℓ − 2)( ℓ + 1) ρ 3 + (2 − ℓ )( ℓ + 1) ρ 2 d dρ − ( ℓ + 1) ρ d 2 dρ 2 − d dρ + ( ℓ + 1) ρ 1 Similarly, for AH ℓ we find bracketleftbigg d dρ − ( ℓ + 1) ρ bracketrightbiggbracketleftbigg d 2 dρ 2 − ℓ ( ℓ + 1) ρ 2 + 1 bracketrightbigg = d 3 dρ 2 − ℓ ( ℓ + 1) ρ 2 d dρ + (2 ℓ + 1)( ℓ + 1) ρ 3 + d dρ − ( ℓ + 1) ρ d 2 dρ 2 − ( ℓ + 1) ρ . Subtracting the two gives H ℓ A − AH ℓ = 2( ℓ + 1) ρ 2 d dρ − 2( ℓ + 1) 2 ρ 2 = 2 2( ℓ + 1) ρ 2 bracketleftbigg d dρ − ( ℓ + 1) ρ bracketrightbigg = 2( ℓ + 1) ρ 2 A. Starting from H ℓ A = AH ℓ + 2( ℓ +1) ρ 2 A , we operate on u ℓ and use H ℓ u ℓ = 0 to find H ℓ u ℓ +1 = 2( ℓ + 1) ρ 2 u ℓ +1 which gives bracketleftbigg H ℓ − 2( ℓ + 1) ρ 2 bracketrightbigg u ℓ +2 = 0 , But we see that H ℓ − 2( ℓ + 1) ρ 2 = d 2 dρ 2 − ℓ ( ℓ + 1) ρ 2 + 1 − 2( ℓ + 1) ρ 2 = d 2 dρ 2 − ( ℓ + 1)( ℓ + 2) ρ 2 + 1 = H ℓ +1 Thus we have proven that H ℓ +1 u ℓ +1 = 0 under the assumption H ℓ u ℓ = 0 ....
View Full Document

This note was uploaded on 11/26/2010 for the course PHYSICS PHYS 852 taught by Professor Michaelmoore during the Spring '10 term at Michigan State University.

Page1 / 7

hw8solutions(first4) - HOMEWORK ASSIGNMENT 8 PHYS852...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online